Power Consumption Comparison of Model Vibratory Unit in Power Supply System with and without Inverter for Frequency Setting of 50 Hz - Ziółkowski, Eugeniusz; Skrzyński, Mateusz (Journal of Casting & Materials Engineering, 2017)
The article presents the instantaneous voltage and current values recorded in the power-supply system of a vibratory unit directly from the power grid or through an inverter for a frequency setting of 50 Hz. The obtained measurement data was used to perform digital signal processing algorithms, calculations of effective voltages, currents, power (active, reactive, and apparent), and power factor tgφ. The results of the calculations were used to compare the two power systems examined.